AI-Driven Risk Management: Transforming Decision-Making in Uncertain Environments - Gracefield, Elowen (Journal of Computer Science and Software Applications, 2023)
Artificial Intelligence (AI) is revolutionizing risk management by enhancing predictive analytics, automating complex processes, and providing real-time insights. This paper explores the integration of AI techniques in risk assessment and mitigation, emphasizing their application across various sectors such as finance, healthcare, and cybersecurity. We propose a novel AI-based risk management framework that leverages machine learning models, anomaly detection, and decision-support systems to proactively identify and address potential risks.